2013
DOI: 10.1115/1.4024123
|View full text |Cite
|
Sign up to set email alerts
|

Design Fixation and Its Mitigation: A Study on the Role of Expertise

Abstract: Engineering idea generation plays a vital role in the development of novel products. Prior studies have shown that designers fixate to the features of example solutions and replicate these features in their ideas. This type of fixation acts as a major hindrance in idea generation, as it restricts the solution space where designers search for their ideas. Building upon the study by Linsey et al. [2010, “A Study of Design Fixation, Its Mitigation and Perception in Engineering Design Faculty,” ASME Trans. J. Mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…However, it might be argued that the experience of variety discourages fixation because of a designers' awareness of available solutions, hence they will manage to avoid fixation. This argument was supported by some researchers, where they found that the high level of expertise hinder fixation compared to lower expertise level (Bilalić et al, 2008a;Viswanathan & Linsey, 2013;Dror ,2011).…”
Section: Factors That Encourage Fixationmentioning
confidence: 86%
See 4 more Smart Citations
“…However, it might be argued that the experience of variety discourages fixation because of a designers' awareness of available solutions, hence they will manage to avoid fixation. This argument was supported by some researchers, where they found that the high level of expertise hinder fixation compared to lower expertise level (Bilalić et al, 2008a;Viswanathan & Linsey, 2013;Dror ,2011).…”
Section: Factors That Encourage Fixationmentioning
confidence: 86%
“…In psychology, fixation was related to functional fixedness , or the Einstellung effect (Bilalić et al, 2016; or the counter sunk effect (Viswanathan & Linsey, 2013). Different classifications were used to categorize fixation .…”
Section: Design Fixationmentioning
confidence: 99%
See 3 more Smart Citations